Phytochemical Moieties From Indian Traditional Medicine for Targeting Dual Hotspots on SARS-CoV-2 Spike Protein: An Integrative in-silico Approach - Umashankar, V.; Deshpande, Sanjay H.; Hegde, Harsha V.; Singh, Ishwar; Chattopadhyay, Debprasad (Frontiers in Medicine, 2021)
SARS-CoV-2 infection across the world has led to immense turbulence in the treatment modality, thus demanding a swift drug discovery process. Spike protein of SARS-CoV-2 binds to ACE2 receptor of human to initiate host invasion. Plethora of studies demonstrate the inhibition of Spike-ACE2 interactions to impair infection. The ancient Indian traditional medicine has been of great interest of Virologists worldwide to decipher potential antivirals. Hence, in this study, phytochemicals (1952 compounds) from eight potential medicinal plants used in Indian traditional medicine were meticulously collated, based on their usage in respiratory disorders, along with immunomodulatory and anti-viral potential from contemporary literature. Further, these compounds were virtually screened against Receptor Binding Domain (RBD) of Spike protein. The potential compounds from each plant were prioritized based on the binding affinity, key hotspot interactions at ACE2 binding region and glycosylation sites. Finally, the potential hits in complex with spike protein were subjected to Molecular Dynamics simulation (450 nanoseconds), to infer the stability of complex formation. Among the compounds screened, Tellimagrandin-II (binding energy of -8.2 kcal/mol and binding free energy of -32.08 kcal/mol) from Syzygium aromaticum L and O-Demethyl-demethoxy-curcumin (binding energy of -8.0 kcal/mol and binding free energy of -12.48 kcal/mol) from Curcuma longa L were found to be highly potential due to their higher binding affinity and significant binding free energy (MM-PBSA), along with favourable ADMET properties and stable intermolecular interactions with hotspots (including the ASN343 glycosylation site). The proposed hits are highly promising, as these are resultant of stringent in silico checkpoints, traditionally used, and are documented through contemporary literature. Hence, could serve as promising leads for subsequent experimental validations.